James C. R. Gill, Dakhleh Oasis and the Western Desert of Egypt under the Ptolemies - Berlin, Andrea M. (Journal of Hellenistic Pottery and Material Culture, 2017)
James Gill’s 2016 monograph, a lightly modiﬁed version of his 2014 PhD thesis, is a terriﬁc example of how to write history from material evidence. His accomplishment is all the more impressive because the evidence in question is pottery derived from excavation and survey, which – as readers of this journal know well – comprises perhaps the most messy, intractable type of material evidence available. In this review article I will first broadcast Gill’s big historical conclusions right up front (for the benefit of any ancient historians sufficiently enlightened to be reading this publication). I will then provide a kind of long-form summary of the evidence he has painstakingly amassed to build his case – and, in the process, take him a little bit to task for the way in which he presents this evidence because it creates unnecessary difficulties for anybody wanting to use this book as a guide. I will close by laying out the full array of Gill’s conclusions regarding Ptolemaic policies and activities in the Western Desert, as these insights are truly outstanding contributions that bear emphasizing.